CONFLICT HANDLING IN RENEWABLE ENERGY COOPERATIVES (RECs): ORGANIZATIONAL EFFECTS AND MEMBER WELL‐BEING. (13th January 2017) - BRUMMER, Vasco; HERBES, Carsten; GERICKE, Naomi
ABSTRACT: We investigate conflict handling in Renewable Energy Cooperatives (RECs) in Germany. Conflict handling in this context shows to be unique due to RECs' business model and the relationship between members and their organization. Unlike in other cooperative firms, most REC members in Germany neither work for their cooperative nor do they receive goods or services from it. We document frequent controversial topics of discussion in annual meetings and how the organizational frame conditions influence modes of conflict handling by the involved parties. Using data gathered by participant observation of the annual meetings of 15 different RECs in southern Germany, we show by a qualitative approach that conflict handling by members of the Executive Board, the Supervisory Board and the rank‐and‐file during the process of decision‐making ranges from highly cooperative to fully Competitive, but these styles tend to converge to collaborative outcomes, reflecting the members' shared commitment to the cooperative principles of the enterprise.